FUZZY CONTROL OF ANTI-LOCK BRAKING SYSTEM AND ACTIVE SUSPENSION IN A VEHICLE (Sciences & Technologie. B, Sciences de l'ingénieur, 2015)
The aim of this paper is to propose robust controllers based on fuzzy logic for an Antilock Brake System (ABS) coupled with an active suspension. The main difficulties of controller design in automotive systems are related to high non-linearities, uncertainties caused by external perturbations and parameter variations which are unknown. The objective of a conventional ABS control system is to rapidly eliminate tracking error between the actual slip ratio and a set reference value in order to bring the vehicle to a stop in the shortest time possible. However, braking time and stopping distance can be reduced even further if the same control system also simultaneously considers the state of the active suspension system.A two degree of freedom quarter car vehicle model is developed along with models for a hydraulic active suspension and an ABS system. The controller was designed by using the fuzzy model control theory and was implemented under the Matlab/Simulink software environment.The simulation results show that for a particular vehicle there exists an optimal application of the suspension force. Compared with an ABS system without combing active suspension, the proposed control scheme can improve braking performance significantly.